Mantanani Island - Mohd. Harun Abdullah; Ismail Ali; Zulherry Isnain; Collin G. Joseph (Penerbit UMS, 2019)
Islands serve an important function to the environment and ecology of their surroundings and being in close proximity of a mainland, help protect the mainland from the harsh effect of natural disasters such as tsunamis. In this book, the island of Mantanani is explored and presented from many aspects; covering the environment, flora and fauna, its history, its inhabitants and finally ecotourism opportunities. The Mantanani island consists of a group of three islands situated off the coast of Kata Belud on mainland Sabah. These small islands are named Mantanani Besar, Mantanani Kecil and Lungisan. The strategic location of this group of islands has created a unique environment opportunity. These islands are well known for dugong sightings and recreational diving especially diving for underwater shipwrecks as the area saw numerous naval battles during the Second World War.